Spillover Effect of US Monetary Policy on the Indonesian Economy - Nuning Trihadmini; R Mahelan Prabantarikso (AIBPM Publisher, 2026)
Post-pandemic monetary tightening in the United States (US) has increased external vulnerabilities for emerging economies, including Indonesia. This study examines the spillover effects of US monetary policy on Indonesia’s financial and real sectors during 2020–2023. Using monthly data, a Vector Autoregression (VAR) model and Forecast Error Variance Decomposition (FEVD) are employed to analyze dynamic shock transmission between US and Indonesian macro-financial variables. The results show that spillovers from US financial variables to Indonesia’s financial sector average 9.23%, exceeding those from US real variables (7.80%). The largest spillovers originate from the Dow Jones Industrial Average (11.62%) and the US 10-year Treasury yield (10.54%). Indonesia’s Jakarta Composite Index (JCI) and exchange rate absorb the strongest external shocks, with spillover values of 10.19% and 9.72%, respectively. In the real sector, the average spillover effect reaches 7.46%, while the Composite Leading Indicator (CLI) records the highest spillover absorption (10.28%). The strongest individual transmission is observed from the US government debt to Indonesia’s CLI, reaching 23.69%. These findings indicate that US monetary policy influences Indonesia mainly through financial-market and expectations channels, highlighting the need to strengthen macro-financial resilience and monitor global forward-looking indicators.